2002
DOI: 10.1270/jsbbs.52.201
|View full text |Cite
|
Sign up to set email alerts
|

Identification of AFLP Markers Favorable to Heterosis in Hybrid Rice.

Abstract: In hybrid rice breeding programs, it is the most important to select donors for improving parental lines and to predict the hybrid performance. In this study, AFLP marker technology and a half-diallel method were used to address these related issues in hybrid rice. Based on the representative heterosis characters representing in the F 1 generation, an innovative method was designed to identify the genetic diversity related to heterosis for yielding with the detected AFLP. The results showed that the genetic di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
24
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 16 publications
1
24
0
2
Order By: Relevance
“…1 has been proposed as a useful tool for hybrid vigor prediction (Melchinger 1999). Several studies reported a positive correlation between genetic distance of parental lines and superior hybrid performance (Liu et al 2002;Barbosa et al 2003). An alternative approach, pioneered by Stuber et al (1992), aims to identify and characterize the quantitative trait loci (QTL) contributing to heterosis, providing also indications about the genetic basis of the phenomenon.…”
mentioning
confidence: 99%
“…1 has been proposed as a useful tool for hybrid vigor prediction (Melchinger 1999). Several studies reported a positive correlation between genetic distance of parental lines and superior hybrid performance (Liu et al 2002;Barbosa et al 2003). An alternative approach, pioneered by Stuber et al (1992), aims to identify and characterize the quantitative trait loci (QTL) contributing to heterosis, providing also indications about the genetic basis of the phenomenon.…”
mentioning
confidence: 99%
“…A number of methods exist to estimate genetic distance based on pedigree data, morphological data, agronomic performance data, biochemical data, and DNA data (Mohammadi and Prasanna, 2003). Several studies have reported a positive correlation between genetic distance of the parental lines and the superior hybrid performance (Liu et al, 2002;Barbosa et al, 2003). However, in maize (Zea mays), heterosis is known to culminate at an optimum of parental genetic distance before declining again (Moll et al, 1965).…”
mentioning
confidence: 99%
“…The heterotic trait is expressed under heterozygosity, mainly in the F 1 generation, resulting from both complementary action and interaction of parental genetic diversity (Liu et al 2002). In general, genetic diversity should be an important basis for heterosis formation, though different results have been reported previously in various crops (Melchinger et al 1990, Zhang et al 1996.…”
Section: Discussionmentioning
confidence: 99%
“…Since there may be only a small difference in the genetic diversity related to heterosis between them, it is much more important to identify the genetic diversity related to heterosis. This genetic diversity should be divided into the favorable and unfavorable categories, which are equally important to heterosis breeding (Liu et al 1998, Liu et al 2002. The desirable genetic diversity will enable to enhance heterosis, while the undesirable genetic diversity will reduce it.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation